Pengaruh Limbah Tahu sebagai Pupuk Organik Cair terhadap Pertumbuhan dan Produksi Tanaman Tomat (Lycopersicum esculentum) dan Pemanfaatannya sebagai Media Pembelajaran - Mitasari Suleman Salamati; Andi Tanra Tellu; Mestawaty Mestawaty; Gamar Binti Non Shamdas (Universitas Tadulako, 2022)
This study aims to explain the effect of tofu waste as liquid organic fertilizer on the growth and production of tomato plants (Lycopersicum esculentum) and its use as a learning media in the form of posters. This research was conducted at the Green House Biology FKIP UNTAD from November 2020 to February 2021. The method used was an experimental method with a completely randomized design (CRD) one factorial experiment consisting of 4 levels of treatment (P0 = control, P1 = 200 ml, P2 = 400 ml, P3 = 600 ml) and 3 replications. Parameters observed in this study were plant height, number of leaves, number of branches, number of fruits, and stem diameter at 15 DAP, 30 DAP, 45 DAP, and 60 DAP. The calculated parameters were the number of fruit and fruit weight at 60 DAP. The results of this study showed that the best growth and production was P1 treatment with a dose of 200 ml of liquid organic fertilizer tofu waste. This can be seen in the analysis of variance for each parameter, namely plant height with Fhit 4.90 > Ftab 4.07, number of branches Fhit 8.14 > Ftab 4.07, number of leaves Fhit 7.13 > Ftab 4.07, stem diameter Fhit 12.92 > Ftab 4.07, number of fruit values Fhit 11.83 > Ftab 4.07, and the weight of the fruit is Fhit 11.36 > Ftab 4.07, then H0 is rejected and H1 is accepted. Thus, it can be concluded that liquid organic fertilizer from tofu waste can affect the growth and production of tomato plants with the best dose of 200 ml at 60 DAP. Based on the validation test and has been tested on students, the overall results of the study are very feasible to be used as learning media with an average percentage of 81.84%.